Pengaruh Meme dan Karakter Virtual Shinna terhadap Kepuasan Informasi Pengguna Instagram BMKG Gowa - Doni Ari Saputra; Yasir Yasir (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Instagram has become a strategic medium for government institutions in delivering public information, particularly weather and disaster-related information that requires speed, clarity, and ease of understanding. The BMKG of Gowa Regency utilizes digital communication innovations through the use of informative memes and a virtual character named Shinna as a visual communication strategy to enhance the effectiveness of information dissemination to the public. This study aims to analyze the influence of meme usage and the virtual character Shinna on the information satisfaction of Instagram users of BMKG Gowa Regency by employing the Stimulus–Response (S–R) theory perspective, which views visual messages as stimuli capable of eliciting cognitive and affective responses from audiences. This research adopts a quantitative approach using a survey method. Data were collected through an online questionnaire with a four-point Likert scale administered to followers of the BMKG Gowa Regency Instagram account who had viewed or interacted with meme content and the virtual character Shinna. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results indicate that the use of memes and the virtual character Shinna has a positive and significant effect on users’ information satisfaction, both partially and simultaneously. Meme usage shows a more dominant influence compared to the virtual character Shinna, while the coefficient of determination (R²) value of 0.834 indicates that both variables explain 83.4% of the variance in users’ information satisfaction. These findings confirm that public communication strategies based on memes and virtual characters are effective in enhancing audience understanding, comfort, and satisfaction with disaster-related information.